Pengaruh Penerapan Inovasi Pelayanan Publik Simpatti (Sistem Informasi Pajak dan Retribusi Terintegrasi ) terhadap Kualitas Pelayanan pada BPPRD Kota Jambi - Imtiyaz Ragbah Fidini; Dahmiri Dahmiri; Maratun Saadah (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This study aims to analyze the effect of the implementation of the Integrated Tax and Retribution Information System (SIMPATTI) on the quality of public services at the Regional Tax and Retribution Management Agency (BPPRD) of Jambi City. The study used a quantitative approach involving 51 respondents who were active users of the SIMPATTI application. Research data were collected through the distribution of questionnaires and structured interviews, then analyzed using a simple linear regression method with the help of SPSS software version 31. The results of the analysis indicate that the implementation of SIMPATTI has a positive and significant effect on improving the quality of public services. This effect is evident in aspects of service speed, ease of access to information, and the level of taxpayer satisfaction with the services provided. These findings confirm that the digitalization of the regional tax system through SIMPATTI is able to create public service governance that is more efficient, transparent, and responsive to community needs, thereby supporting improved bureaucratic performance and public trust in local government.